Composition and functional properties of yam bean (Pachyrhizus spp.) seed flour - Kisambira, A.; Muyonga, John H.; Byaruhanga, Y.B.; Tukamuhabwe, Phineas; Tumwegamire, Silver; Grüneberg, W.J. (Scientific Research Publishing, Inc., 2015)
Yam bean (Pachyrhizus spp.) is legume crop that not only produces edible roots but also has a high yield of unutilized seeds. Although the yam bean seeds are rich in protein, they are not used due to a high content of toxic rotenone. In this study, yam bean seeds were detoxified and the nutritional and functional properties of their protein determined to assess the proteins’ potential for applications. Seeds of 10 accessions (2 accessions of P. erosus, 4 accessions of P. ahipa and 4 accessions of P. tuberosus) were analyzed for proximate composition, pasting and functional properties (bulk density, least gelation concentration, water absorption capacity, oil absorption capacity, emulsifying capacity, emulsion stability, foaming capacity, foam stability and protein solubility). The results showed that yam bean seeds contained: 29.2 - 32.1 g/100g proteins, 31.3 - 33.0 g/100 g carbohydrates, 24.1 - 25.6 g/100g total fat, 7.5 - 8.1 g/100g crude fiber and 3.4 - 4.1 g/100g ash. The defatted P. erosus seed flour contained 45.6 - 48.8 g/100g protein, 32.6 - 36.5 g/100g total carbohydrate, 6.7 - 7.1 g/100g crude fiber, 6.0 - 6.4 g/100g ash and 5.2/100 g crude fat. The defatted yam bean seed flour exhibited relatively high protein solubility (68.0% - 70.4%), least gelation concentration (14%), water absorption capacity (2.8% - 2.9%) and oil absorption capacity (1.5%). The defatted flour exhibited emulsifying capacity of 35.7% - 36.0%, emulsion stability of 33.2% - 33.5%, foaming capacities of 42% and foam stability of 25.1% - 25.8%. With respect to pasting properties, the defatted yam bean seed flours exhibited pasting temperature of 80.0˚C - 81.3˚C, peak viscosity of 145.5 - 146.7 RVU, trough viscosity of 95.1 - 102.0 RVU, break down of 43.5 - 51.6 RVU, set back of 252.9 - 258.1 RVU and final viscosity of 348 - 360 RVU. The results show that yam bean seed has potential for use in both food and nonfood applications.